Improving Students’ Ability In Reading Narrative Text By Using Reading Aloud And Question And Answer Technique At Smp Negeri 1 Langowan - Tini Mogea (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is intended to prove whether reading aloud and the question-and-answer technique are effective or not in improving students’ ability to read narrative text at SMP Negeri 1 Langowan. This research is classified as